Low complexity user and spatial detection by using AD8313 evaluation board - Hock G.C.; Raymond W.J.K.; Kiong T.S.; Chakrabarty C.K. (2023)
In this paper, a relatively low cost, simple user and spatial detection with AD8313 evaluation board is described. 16-element linear array antennas are designed in order to operate at frequency of 457 MHz for the rural communication network. A testing-bed with simple arrangement is setup in order to validate the proposed method. The array antennas are used as radar and enclosed a wide scanning angle of 120 degree via a mechanical motor. And, the AD8313 evaluation board is use to convert the radio frequency signal to a direct current output. The outputs of the board are measured with an oscilloscope. 2011 IEEE.